PENGARUH GOOD CORPORATE GOVERNANCE (GCG) DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN (STUDI EMPIRIS PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2014 - admin, RININGGO ADITYA RYANTO B41111113 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
This research aims to analyze characteristic factors of good corporate governance ( GCG ) and company size ( CZ ) in companies that can affect the company performance ( tobins’q ) mining companies coal sector listed on the indonesia stock exchange. Characteristic factors of good corporate governance used between other is board of directors ,board of commissioners , and company size. The population of this research are companies in coal mining sector listed on the indonesia stock exchange where these companies had issued annual report and  sustainability reports in 2011 until 2014. Total research sample are 15 companies determined through purposive sampling. This research analyzed data use test descriptive test the assumption classical and the testing of hypotheses with the methods linear regression multiple use IBM SPSS 23. The result of the research indicated that the variable board of directors do not have significant impact on the company performance while variable the board of commissioners and the company size have significant effect against the company performance sector coal mining companies listed on the indonesian stock. Keywords : Good Corporate Governance (GCG), board of directors, board of commissioners , Company Size (CZ), Company Performance (Tobins’Q)